Progress of important clinical research on breast cancer in China in 2024 - YANG Xin, SHI Qianfeng, LIU Qiang (Zhongguo aizheng zazhi)
Breast cancer, is the cancer type with highest incidence rate in women globally. To improve the treatment for breast cancer patients, Chinese scientists have done extensive research on breast cancer. Reviewing the progress made in 2024, Chinese scholars have achieved significant advancements in various aspects of breast cancer research. In the field of surgery, new optical imaging techniques have aided the accurate assessment of surgical margins, and targeted axillary dissection (TAD) continues to provide evidence-based support for de-escalation therapy in surgery. Radiomics combined with artificial intelligence (AI) also assists in surgical decision-making. In targeted therapy, tyrosine kinase inhibitors (TKIs) have shown excellent clinical outcomes. The PILHLE-001 study explored new subtypes for the use of pyrotinib, offering new therapeutic approaches for luminal/human epidermal growth factor receptor 2 (HER2) low breast cancer. The efficacy and safety of anlotinib and apatinib are also reliable. Dual-targeted HER2 regimens in neoadjuvant therapy (NAT) and adjuvant therapy for early HER2-positive patients have demonstrated significant benefits over single-target regimens, improving survival rates. Various antibody-drug conjugates (ADCs) have shown significant clinical applicability, enhancing patient survival benefits, and novel drugs developed in China are making their way onto the international stage, increasing their global influence. Additionally, immunotherapy and precision treatment based on Fudan subtypes have shown varied degrees of survival improvement. In chemotherapy, different NAT strategies have been explored, offering more treatment options for doctors and patients. In endocrine therapy, the critical role of CDK4/6 inhibitors (CDK4/6i) in advanced hormone receptor positive/HER2-negative breast cancer has been further solidified, and issues concerning previously undetermined drug formulations of gonadotrophin releasing hormone analogue (GnRHa) have been examined. In radiotherapy, local radiotherapy combined with targeted therapy has significantly extended the survival of HER2-positive breast cancer patients with brain metastases, and optimizations have been made regarding the cardiotoxic side effects associated with radiotherapy. This article summarized the key clinical research on breast cancer in China in 2024, providing a reference for scholars and experts in related fields.